The CFD modeling of bund overtopping phenomena and prediction of dynamic pressure on the bund. (January 2022) - Huo, Jiali; Wang, Zhi; Luan, Xiaoyang; Jing, Mingju; Hou, Shuya; Jiang, Juncheng; Zhang, Bin
Abstract: The storage tank of hazardous materials is usually equipped with bund system for hazard mitigation in case of a release incident. The catastrophic release incident requires an effective bund system to control overtopping and withstand the liquid dynamic pressure. This work developed three-dimensional (3D) Computational Fluid Dynamic (CFD) models based on RNG k-ε and Large Eddy Simulation (LES) model, respectively. These two CFD models were compared in terms of overtopping fraction and flow behavior, and both were validated against the experimental results. The validated 3D RNG k-ε model was used to investigate the flow behavior and dynamic pressure of the circular and square bund. Based on the results, the 3D RNG k-ε model is slightly better than the 3D LES model in terms of predicting the overtopping fraction and the height of central spike in this study; the 3D RNG k-ε model predicts the height of central spike better than the 2D model, and has the advantage to simulate complex bund design; the findings on flow behavior and dynamic pressure of the circular and square bund will help provide a scientific basis to design the bund system for minimizing the overtopping fraction and withstanding the liquid dynamic pressure. Highlights: Development and validation of three-dimensional Computational Fluid Dynamic models based on RNG k-ε and LES model. Investigation of the flow behavior and dynamic pressure on the bund wall for circular and square bunds. The model provides a scientific basis for the bund design to minimize overtopping and withstand liquid dynamic pressure.